An ethics framework for the transition to an operational learning healthcare system - Marieke J Hollestelle; Rieke van derGraaf; Miriam CJM Sturkenboom; Johannes JM vanDelden (Wiley, 2024)
Abstract Introduction While Learning Healthcare Systems (LHSs) have received increasing attention in health care and research, the amount of operational LHSs remains limited. Given the investment of resources in these projects, a moral responsibility to pursue the transition toward an LHS falls on projects and their participating stakeholders. This paper provides an ethics framework for projects that have taken steps toward building an LHS and are in the position to transition to an operational LHS. Method To articulate relevant ethical requirements, we analyze established ethics frameworks in the fields of LHSs, data‐intensive health research, and transitioning or innovating health systems. The overlapping content and shared values are used to articulate overarching ethical requirements. To provide necessary context, we apply the insights from the analysis to the Innovative Medicines Initiative ConcePTION project. This project is specifically designed to generate knowledge on the safety of medications used during pregnancy and lactation through the establishment of an LHS. Results Upon analyzing the consulted frameworks, we identified four overlapping ethical requirements that are also of significant relevance within the scope of our ethics framework. These requirements are: (1) public benefit and favorable harm-benefit ratio; (2) equity and justice; (3) stakeholder engagement; and (4) sustainability. Additionally, we apply these ethical requirements to the context of an LHS for pregnant and lactating people. Conclusion Although tailored to the context of pregnancy and lactation, our ethics framework can provide guidance for the transition to an operational LHS across diverse healthcare domains.